Comparison of Closed-loop and Open-loop Models in the Assessment of Cardiopulmonary and Baroreflex Gains - Takalo, R.; Saul, J. P.; Korhonen, I. (Methods of Information in Medicine, 2004)
Objectives: Both open- and closed-loop models of beat-to-beat cardiovascular control have been suggested. We tested whether the modelling yields different results with real data while assessing cardiopulmonary and baroreflex gains.Methods: Two autoregressive models are described to resolve causal relationships between systolic blood pressure (SBP), RR-interval (RRI) and instantaneous lung volume (ILV): a closed-loop model which takes into account both the RRI changes induced by changes in SBP and the SBP changes mediated by changes in RRI, and an open-loop model which does not have a link from RRI to SBP. The performance of the models was compared in 14 healthy men in supine and standing positions under control conditions and under conditions of β-sympathetic and parasympathetic pharmacological blockades. Transfer function gains were computed from ILV to RRI (cardiopulmonary gain) and from SBP to RRI (baroreflex gain). The measurements were done under controlled random-interval breathing.Results: The gains identified by the open-loop model tended to be higher than those from the closed-loop model, but the differences did not reach statistical significance. Importantly, the two models discriminated the changes in transfer gains between different interventions equally well.Conclusions: Because the interactions between SBP and RRI occur physiologically in a closed-loop condition, the closed-loop model provides a theoretical advantage over the open-loop model. However, in practise, it seems to be little reason to select one over the other due to methodological errors when estimating cardiopulmonary or baroreflex transfer gains.
Keywords: Multivariate; modelling; baroreceptors; blood pressure; heart rate